Oral liarozole in the treatment of patients with moderate/severe lamellar ichthyosis: results of a randomized, double‐blind, multinational, placebo‐controlled phase II/III trial. (1st January 2014) - Vahlquist, A.; Blockhuys, S.; Steijlen, P.; van Rossem, K.; Didona, B.; Blanco, D.; Traupe, H.
Summary: Background: Oral liarozole, a retinoic acid metabolism‐blocking agent, may be an alternative to systemic retinoid therapy in patients with lamellar ichthyosis. Objective: To demonstrate the efficacy and safety of once‐daily oral liarozole in the treatment of moderate/severe lamellar ichthyosis. Methods: This was a double‐blind, multinational, parallel phase II/III trial (NCT00282724). Patients aged ≥ 14 years with moderate/severe lamellar ichthyosis [Investigator's Global Assessment (IGA) score ≥ 3] were randomized 3 : 3 : 1 to receive oral liarozole (75 or 150 mg) or placebo once daily for 12 weeks. Assessments included: IGA; a five‐point scale for erythema, scaling and pruritus severity; Short Form‐36 health survey; Dermatology Life Quality Index (DLQI); and safety parameters. The primary efficacy variable was response rate at week 12 (responder: ≥ 2‐point decrease in IGA from baseline). Results: Sixty‐four patients were enrolled. At week 12, 11/27 (41%; liarozole 75 mg), 14/28 (50%; liarozole 150 mg) and one out of nine (11%; placebo) patients were responders; the difference between groups (liarozole 150 mg vs. placebo) was not significant ( P = 0·056). Mean IGA and scaling scores decreased from baseline in both liarozole groups at weeks 8 and 12 vs. placebo; erythema and pruritus scores were similar between treatment groups. Improvement in DLQI score was observed in both liarozole groups. Treatment with liarozole for 12 weeks was well tolerated. Conclusions: The primary efficacy variable did not reach statistical significance, possibly owing to the small sample size following premature termination. However, once‐daily oral liarozole, 75 and 150 mg, improved scaling and DLQI and was well tolerated in patients with moderate/severe lamellar ichthyosis.